A Practical Study on Using Computer Technology to Assist College English Teaching. Issue 3 (May 2021) - An, Kun
Abstract: With the development of science and technology, traditional teaching is also innovating and researching. At present, computers are widely used in different industries. Nowadays, colleges and universities in China are changing the traditional teaching mode to the teaching mode supplemented by computer. College English, as a compulsory basic subject course for every major in college, is a teaching mode supplemented by computer technology, which changes the previous teaching mode and makes college English teaching classroom one of the favorite classes for college students. This paper explores and studies the teaching mode, teaching method and teaching curriculum of college English supplemented by computer.